2020
DOI: 10.1002/jsfa.10774
|View full text |Cite
|
Sign up to set email alerts
|

Differences in oxidative susceptibilities between glycerophosphocholine and glycerophosphoethanolamine in dried scallop (Argopecten irradians) adductor muscle during storage: an oxidation kinetic assessment

Abstract: BACKGROUND Phospholipids, the main lipid component in marine shellfish, mainly comprise glycerophosphocholine (GPC) and glycerophosphoethanolamine (GPE). GPC and GPE in marine shellfish, especially scallop, carry n‐3 long‐chain polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), although different types of glycerophospholipids (GP) have different health benefits on human health. Moreover, different GP subclasses such as GPC and GPE have different oxidative susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Dried aquatic products are widely consumed in the market due to the easy transportation and storage with the long shelf-life (Wang et al, 2011). However, lipid oxidation still occurred during the storage of dried aquatic products such as clam, scallop and shrimp products due to the unsaturated fatty acid components (Xie et al, 2018(Xie et al, , 2021Li et al, 2019). Our previous study observed that PUFAs accounted for 39.04-48.77% of total FAs in oyster lipid; among them, the percentages of EPA and DHA were 12.11-27.78% and 10.96-17.04% respectively (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dried aquatic products are widely consumed in the market due to the easy transportation and storage with the long shelf-life (Wang et al, 2011). However, lipid oxidation still occurred during the storage of dried aquatic products such as clam, scallop and shrimp products due to the unsaturated fatty acid components (Xie et al, 2018(Xie et al, , 2021Li et al, 2019). Our previous study observed that PUFAs accounted for 39.04-48.77% of total FAs in oyster lipid; among them, the percentages of EPA and DHA were 12.11-27.78% and 10.96-17.04% respectively (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dominant GP molecular species possessed PUFA, mainly DHA and EPA (Liu et al, 2020). It was worth mentioning that PUFAs of different esterification forms in dried scallop have different oxidative susceptibilities (Xie et al, 2020(Xie et al, , 2021. In detail, TAG in the oyster lipid was more susceptible to oxidative degradation than PL, and GPE exhibited poorer oxidative stability than GPC due to the amino group in structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it also plays a crucially important role in improving blood lipids, fighting fatigue, and enhancing immunity. Adductor muscle, the main edible part of scallop, which could be made into massive delicious dishes after being dried, which is highly sought after by some food lovers [5][6][7][8]. The Scallop Skirt could be made into delicious seafood soy sauce, a good helper for stir-fry seasoning, and could also serve as processed into raw materials for bait.…”
Section: Introductionmentioning
confidence: 99%